Determinants of Financial Sustainability (An Empirical Analysis of Co-operative Rural Banks in Jaffna District, SriLanka) - Ranjani, R. P. C.; Prahalathan , B. (Gyan Management Journal, 2011)
This study examines the determinants of financial sustainability of the Co -operative rural banks in ]affna District, Sri Lanka. The efficiency determinants are administrative efficiency,financial efficiency, staff efficiency and operating efficiency. Financial sustainability is measured by financial self sufficiency. Administrative and financial efficiency are measured by administrative expenses ratio and real portfolio yield respectively. Staff efficiency is measured by number of active loan clients per staff member ratio, number of active loan clients per loan officers’ ratio and gross portfolio outstanding per loan officer ratio. Operating efficiency is measured by operating efficiency ratio. Financial performance is measured by financial self sufficiency ratio. The study finds administrative efficiency; financial efficiency and gross portfolio outstanding per loan officer ratio are significant determinants of financial self-sufficiency. Further study finds positive relationship between financial self- sufficiency and number of active loan clients per staff member ratio and number of active loan clients per loan officers’ ratio.